SEBARAN STATUS BAHAN ORGANIK SEBAGAI DASAR PENGELOLAAN KESUBURAN TANAH PADA PERKEBUNAN TEBU (Saccharum officinarum L.) LAHAN KERING BERPASIR DI PT. PERKEBUNAN NUSANTARA X, DJENGKOL-KEDIRI - Firda Inayati Harista; s Soemarno (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
Application of organic matter is done as one of the basic activities of soil fertility management in sugarcane plantation. Application of organic matter at the planting site can be done based on the status of soil organic matter from map of the status of soil organic matter. Differences in the status of soil organic matter can be caused by differences of soil management, such as compost, liquid organic fertilizer and trashes application. As a basic activity of soil fertility management, organic matter application has a significant influence in the availability of soil-N, C/N ratio and soil pH. Content of soil organic matter in the sugarcane land are ranged from 0.9% to 3.5%, and distributed from â€œvery-lowâ€ to â€œmoderateâ€ status.